2015
DOI: 10.1149/2.0241503jss
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of pH on Sapphire Chemical Mechanical Polishing

Abstract: In this paper, the effect of pH on sapphire chemical mechanical polishing (CMP) was investigated. The sapphire removal rate increased with ascending pH until 8. To investigate the electrostatic force between colloidal silica abrasive and sapphire surface, the zeta potential of sapphire surface and colloidal silica abrasive were studied. The sapphires immersed into the slurry containing 20 wt% colloidal silica were observed with scanning electron microscopy (SEM). For further insights into the mechanism of sapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…Chemical Mechanical Planarization (CMP), a very critical and important step in semiconductor device fabrication, uses a combination of mechanical and chemical reactions to remove the surface structure, leaving a plane and damage free surface. Surface planarization of materials, including Al 2 O 3 , SiO 2 , InP, SiC and GaAs, using Colloidal SiO 2 based Slurries were studied [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical Mechanical Planarization (CMP), a very critical and important step in semiconductor device fabrication, uses a combination of mechanical and chemical reactions to remove the surface structure, leaving a plane and damage free surface. Surface planarization of materials, including Al 2 O 3 , SiO 2 , InP, SiC and GaAs, using Colloidal SiO 2 based Slurries were studied [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Khushnuma et al reported maximum MRR of ∼85 nm/hr on polar GaN wafer for slurry containing 3.75 wt% Al 2 O 3 and 0.3 M oxidizer concentration but no surfactant or electrolyte in the slurry. Material removal rates of 1.14 m/hr and 1.85 m/hr for non-polar (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) and semi-polar (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) GaN surfaces, respectively, have been achieved using an abrasive free chemical mechanical planarization [20,21]. Studies of surfactant adsorption have typically focused on conditions where there is clear electrostatic driving force for adsorption; i.e., where surfactants have opposite charge to those of metal oxide surfaces [22].…”
Section: Introductionmentioning
confidence: 99%
“…The mean particle size of colloidal silica affected by the pH indicated that the removal rate of sapphire was marginally affected by mechanical abrasion. 12 Sumi et al (2012) observed that all the commercially available CS dispersions show particle size of 15±5 nm in transmission electron microscopy. As shown in the TMA curve in Figure 1, Dmax of TEMs increased as the particle size of CS decreased.…”
Section: Methodsmentioning
confidence: 99%
“…This may be due to the surface saturation of the particles and excess (OH À ions) charge working against the stability of the dispersion. 47 The Ag NPs with native surfaces were highly sensitive in the basic medium and got oxidized in an excess of NH 4 OH solution. Therefore, they were likely to form unstable AgOH.…”
Section: Stability In Polar Solventsmentioning
confidence: 99%